Catalyzing urea hydrolysis using two-step microbial-induced carbonate precipitation for copper immobilization: Perspective of pH regulation - Xue, Zhong-Fei; Cheng, Wen-Chieh; Wang, Lin; Xie, Yi-Xin (Frontiers in Microbiology, 2022)
Microbial induced carbonate precipitation (MICP) has recently applied to immobilise heavy metals towards preventing their threats to public health and sustainable development of surrounding environments. However, for copper metallurgy activities higher copper ion concentrations cause the ureolytic bacteria to lose their activity, leading to some difficulty in forming carbonate precipitation for copper immobilisation (referred to also as ‘biomineralisation’). A series test tube experiments were conducted in the present work to investigate the effects of bacterial inoculation and pH conditions on the copper immobilisation efficiency. The numerical simulations mainly aimed to compare with the experimental results to verify its applicability. The copper immobilisation efficiency was attained through azurite precipitation under pH in a 4-6 range, while due to Cu2+ migration and diffusion, it reduced to zero under pH below 4. In case pH fell within a 7-9 range, the immobilisation efficiency was attained via malachite precipitation. The copper-ammonia complexes formation reduced the immobilisation efficiency to zero. The reductions were attributed either to the low degree of urea hydrolysis or to inappropriate pH conditions. The findings shed light on the necessity of securing the urease activity and modifying pH conditions using the two-step biomineralisation approach while applying the MICP technology to remedy copper-rich water bodies.